Analisis Kelayakan Usaha Getah Pinus KPHL Kulawi Kabupaten Sigi - Masserang, Busranuddin Daeng; Umar, Syukur; Rachman, Imran (Mitra Sains, 2020)
This study aims to determine the business feasibility of pine resin (Pinus merkusii Jungh et de Vriese) at protected forest management unit or KPHL Kulawi and determine the effect of increasing the cost of managing pine resin on business feasibility through sensitivity analysis. The value of input and output at the time of the study was considered as a constant price with units of costs and revenues generated in units of Rp/Ha/Year. The analysis was carried out using the formula of investment feasibility criteria namely Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR) and sensitivity analysis to determine the strength of the business in the event of increased costs. This study uses Bank Indonesia's annual average interest rate of 6.75%, obtained NPV value of Rp.296.870.072,20, BCR value is greater than 1 (one) that is 2.23 and large IRR value is 39,63%, which is greater than the investment interest rate. Based on the investment eligibility criteria, the pine sap business fulfils the feasible requirements to run. The results of the sensitivity analysis show the pine sap business in the Kulawi KPHL is not strong in facing a 120% increase in costs, an NPV value < 0 and a BCR value decrease below zero, which means that the pine sap investment is not feasible to continue.